1978
DOI: 10.1111/j.1550-7408.1978.tb04403.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Amphizoic Amebae in Domestic Animals

Abstract: Random examination of domestic animals revealed the frequent presence of free-living amebae in their bodies. In diseased or dead cows, dogs, pigs, rabbits, pigeons, and turkeys 15 strains of amebae were found, belonging to the genera Acanthamoeba (A. polyphaga), Hartmannella (H. vermiformis), and Vahlkampfia (V. avara, V. enterica, V. inornata). They were usually accompanied by other infectious agents in different parts of the host bodies. Pathogenicity of 3 isolates could not be demonstrated by inoculation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Although Fields et al (1989) mentioned temperatures reaching 52ºC, ATCC Hartmannella strains, including one deposited originally as H. thermophila (strain LCD-1A), are cultured at 25ºC. The culturing experiments made by Kadlec (1978) with several Hartmannella vermiformis strains isolated from domestic animals showed that amoebae adapted to room temperatures degenerate upon prolonged culturing at 37ºC. The extreme high temperature tolerance was proved in four Hartmannella strains isolated from hot-water systems by culturing them at 53ºC (Rohr et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Fields et al (1989) mentioned temperatures reaching 52ºC, ATCC Hartmannella strains, including one deposited originally as H. thermophila (strain LCD-1A), are cultured at 25ºC. The culturing experiments made by Kadlec (1978) with several Hartmannella vermiformis strains isolated from domestic animals showed that amoebae adapted to room temperatures degenerate upon prolonged culturing at 37ºC. The extreme high temperature tolerance was proved in four Hartmannella strains isolated from hot-water systems by culturing them at 53ºC (Rohr et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The data collected on a variety of bacterial endocytobionts in Hartmannella vermiformis Page, 1967, and the recognition of its special role in the propagation of Legionnaires' disease, provide evidence that these amoebae are more important as hosts of true or potential pathogens of humans than as primary agents of human diseases (Fields et al 1989, Kuchta et al 1993, Brieland et al 1996, Fields 1996, Horn et al 2000. Scarce data available on Hartmannella infections in animals including fish point to a similar situation (Kadlec 1978, Bomhard et al 2002, Telford and Bursey 2003, Dyková and Lom 2004. Nevertheless, pathogenicity of Hartmannella spp.…”
mentioning
confidence: 99%
“…These amoebae can survive severe conditions by forming resistant cysts. Some are of medical importance as causative agents of infections and disease in humans (Cerva 1980;Martinez 1985;Ma et al 1990) and animals (Kadlek 1978). Naegleria fowleri produces primary amoebic meningoencephalitis (PAM).…”
Section: Introductionmentioning
confidence: 99%
“…1). Alternatively, it is also plausible that the oxidative DNA glycosylases in Mimivirus were either acquired from or transferred to a higher eukaryote since the mimiviral host, Acanthamoeba, is an opportunistic pathogen in vertebrates including humans [41,42] and the mimiviral Nei proteins share sequence homology to the NEIL proteins in vertebrates (Fig. 1). …”
Section: Origin Of the Oxidative Dna Glycosylases In Mimivirusmentioning
confidence: 99%